Fiscal composition and long-term growth - Afonso, António (2022)
We assess the fiscal composition–growth nexus, using a large country panel, accounting for the usually encountered econometric pitfalls. Our results show that revenues have no significant impact on growth whereas expenditures have negative effects. The same is true for the OECD with the addition that government revenue has a negative impact on growth. From our results, taxes on income are less for growth enhancing, as well as public wages, interest payments, subsidies and government consumption, while spending on education and health boosts growth.